Faith-Based Social Responsibility: Catholic Ethics and Community-Based Tourism in Ngu Hiep Islet, Dong Thap Province, Vietnam - Chung , Khang Le; Nguyen, Ngoc Anh (Millah: Journal of Religious Studies, 2026)
This article examines how Catholic ethical principles are transformed into faith-based social responsibility within the context of community-based tourism development in Ngu Hiep Islet, a distinctive ecological–cultural area in the Mekong Delta, Vietnam. The study employs the theoretical framework of Corporate Social Responsibility (CSR) alongside Catholic Social Teaching (CST) to elucidate the interconnections among faith, ethical conduct, and sustainable development. Qualitative data were collected through 20 in-depth interviews, participant observation, and analysis of secondary documents within the local Catholic community. The findings reveal that faith not only shapes spiritual life but also frames labor values, a service-oriented mindset, and environmental awareness. The parish operates as a moral–social institution that coordinates and supervises community behavior in accordance with the principle of “serving in love.” Building on these insights, the article proposes a Faith-Based CSR model as an alternative approach to conventional CSR, thereby offering a theoretical lens through which to understand the role of religion in promoting sustainable community-based tourism and fostering an ethical social order in rural Vietnam.